The effect of thermal ageing on electrical and mechanical properties of thermoplastic nanocomposite insulation of power high-voltage cables - El Sherkawy, Eman; Nasrat, Loai S.; Rihan, Mahmoud (Національний технічний університет "Харківський політехнічний інститут", 2024)
This research explores the thermal ageing influence on the Low Density Polyethylene (LDPE) dielectric properties, which is utilised as electrical insulation in high-voltage cables. An accelerated thermal ageing test was done at four temperature ranges ranging from 25 °C to 120 °C to define the degree of material deterioration under thermal ageing and to prevent its failure. LDPE composite samples were made by adding aluminium oxide (Al2O3) inorganic filler in two different grain sizes (nano and micro) with various concentrations. The effect of adding inorganic filler on the acceleration of the thermal ageing of the polymer was studied by heating the samples for different periods of time and measuring the dielectric strength of the samples. The obtained results show that thermal ageing considerably affects the electrical properties of the material. The LDPE/Al2O3 nanofiller sample has the highest dielectric strength value at different temperatures. Thermogravimetric analysis was used to investigate the thermal characteristics of materials. The mechanical characteristics of LDPE polymer are studied using tensile strength and elongation at break tests.

У цьому дослідженні вивчається вплив термічного старіння на діелектричні властивості поліетилену низької щільності (LDPE), який використовується як електрична ізоляція у високовольтних кабелях. Випробування на прискорене термічне старіння було проведено в чотирьох температурних діапазонах від 25 до 120 °C, щоб визначити ступінь руйнування матеріалу при термічному старінні і запобігти його виходу з ладу. Композитні зразки LDPE були виготовлені шляхом додавання неорганічного наповнювача з оксиду алюмінію (Al2O3) з двома різними розмірами зерен (нано та мікро) у різних концентраціях. Вплив додавання неорганічного наповнювача на прискорення термічного старіння полімеру вивчали шляхом нагрівання зразків протягом різних періодів часу та вимірювання діелектричної міцності зразків. Отримані результати показують, що термічне старіння істотно впливає на електричні властивості матеріалу. Зразок нанонаповнювача LDPE/Al2O3 має найбільше значення діелектричної міцності за різних температур. Термогравіметричний аналіз використовувався для дослідження термічних характеристик матеріалів. Механічні характеристики полімеру LDPE вивчаються з використанням випробувань на міцність на розрив та подовження при розриві.
Keywords: low density polyethylene; nano filler; micro filler; dielectric strength; thermal ageing; thermogravimetric analysis; поліетилен низької щільності; нанонаповнювач; мікронаповнювач; діелектрична міцність; термічне старіння; термогравіметричний аналіз